Anti-fragmentation: an incomplete diagnosis and wrong solution - Marek Dąbrowski (Center for Social and Economic Research (CASE), 2023)
The euro area suffers from excessive public debt, which is the primary cause of the so-called fragmentation. It should be remedied by fiscal consolidation instead of the quasi-fiscal activities of the European Central Bank, which are inconsistent with its legal status, compromise its independence and undermine its price stability mandate. When targeted market intervention is necessary, it should be provided by the European Stability Mechanism. This paper was provided by the Policy Departmentfor Economic, Scientific and Quality of Life Policies at the request of the Committee on Economic and Monetary Affairs (ECON) ahead of the Monetary Dialogue with the ECB President on 26 September 2022.
Keywords: E58; F45; H62; H63; 330; European Central Bank; European Union; euro area; fiscal discipline; public debt; Transmission Protection Mechanism; Securities Market Programme; Outright Monetary Transactions; Emergency Liquidity Assistance; fragmentation; central bank independence